Clinical presentation and molecular characterization of a novel patient with variant POC1A‐related syndrome. Issue 4 (13th January 2021) - Majore, Silvia; Agolini, Emanuele; Micale, Lucia; Pascolini, Giulia; Zuppi, Paolo; Cocciadiferro, Dario; Morlino, Silvia; Mattiuzzo, Matteo; Valiante, Michele; Castori, Marco; Novelli, Antonio; Grammatico, Paola
Abstract: Biallelic pathogenic variants in POC1A result in SOFT (S hort‐stature, O nychodysplasia, F acial‐dysmorphism, and hypoT richosis) and variant POC1A‐related (vPOC1A) syndromes. The latter, nowadays described in only two unrelated subjects, is associated with a restricted spectrum of variants falling in exon 10, which is naturally skipped in a specific POC1A mRNA. The synthesis of an amount of a POC1A isoform from this transcript in individuals with vPOC1A syndrome has been believed as the likely explanation for such a genotype–phenotype correlation. Here, we illustrate the clinical and molecular findings in a woman who resulted to be compound heterozygous for a recurrent frameshift variant in exon 10 and a novel variant in exon 9 of POC1A . Phenotypic characteristics of this woman included severe hyperinsulinemic dyslipidemia, acanthosis nigricans, moderate growth restriction, and dysmorphisms. These manifestations overlap the clinical features of the two previously published individuals with vPOC1A syndrome. RT‐PCR analysis on peripheral blood and subsequent sequencing of the obtained amplicons demonstrated a variety of POC1A alternative transcripts that resulted to be expressed in the proband, in the healthy mother, and in controls. We illustrate the possible consequences of the two POC1A identified variants in an attempt to explain pleiotropy in vPOC1A syndrome. Abstract :